2007
DOI: 10.22329/jtl.v4i2.120
|View full text |Cite
|
Sign up to set email alerts
|

Some Thoughts on Qallunaat Teacher Caring in Nunavut

Abstract: Qallunaat (non-Inuit) teaching Inuit students in Nunavut risk being agents of the continuing colonialism of EuroCanadian schooling (Berger, 2005). I argue that for a Qallunaat teacher to be a caring teacher this and related issues must be faced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…These comments are consistent with Berger's (2007) reflections about teacher expectations and positive learning environments for Indigenous settings. He suggests that a warm and caring environment where a teacher is seen as part of 'the team' and maintains high expectations for all students and takes into consideration their diversity and how this will be accommodated, is essential for supporting learning.…”
Section: Right From the Beginning I Knew This Year Was Going To Be Gosupporting
confidence: 81%
“…These comments are consistent with Berger's (2007) reflections about teacher expectations and positive learning environments for Indigenous settings. He suggests that a warm and caring environment where a teacher is seen as part of 'the team' and maintains high expectations for all students and takes into consideration their diversity and how this will be accommodated, is essential for supporting learning.…”
Section: Right From the Beginning I Knew This Year Was Going To Be Gosupporting
confidence: 81%
“…Wotherspoon (2006) noted that cultural relevance in terms of pedagogies and materials might not be sufficient: "For any teacher working in an Aboriginal community context, there are strong pressures to transform their actions well beyond the simple introduction of curricular materials and pedagogical styles deemed appropriate for Aboriginal learners" (p. 677). We agree with Wotherspoon that more is needed than appropriate reading materials, for example, and also with Berger (2007), who found that good intentions and caring about one's students are not enough. While these are important, they must be underpinned by an awareness of why change is needed, and what more is needed.…”
supporting
confidence: 74%
“…Staying with it, whether as a teacher educator in a program such as ours, or as an ECT in a northern community, calls for particular qualities of perseverance and flexibility. Berger (2007) suggested, "A high level of commitment, but also reflection, growth, advocacy, and collaboration with Inuit [and other Indigenous communities], is needed" (p. 1).…”
mentioning
confidence: 99%
“…The creation of the Nunavut Education Act in 2006 was the result of community consultations and contains the community's expectations for education (Berger, 2007). The control of education at the community level is understood to be of the utmost importance if education is to fulfill its promise in Nunavut (Berger, 2007, McGregor, 2010.…”
Section: Education In Nunavut Todaymentioning
confidence: 99%
“…The creation of the Nunavut Education Act in 2006 was the result of community consultations and contains the community's expectations for education (Berger, 2007). The control of education at the community level is understood to be of the utmost importance if education is to fulfill its promise in Nunavut (Berger, 2007, McGregor, 2010. However, the assimilation of Inuit continues because the schools remain southern models, and are predominately staffed by Qallunaat, resulting in curriculum, resources, and teaching methods being saturated with Qallunaat culture and social norms (Berger, 2007).…”
Section: Education In Nunavut Todaymentioning
confidence: 99%